2021
DOI: 10.3390/v13040539
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine Inhibits SARS-CoV-2 In Vitro

Abstract: Since the SARS-CoV-2 pandemic started in late 2019, the search for protective vaccines and for drug treatments has become mandatory to fight the global health emergency. Travel restrictions, social distancing, and face masks are suitable counter measures, but may not bring the pandemic under control because people will inadvertently or at a certain degree of restriction severity or duration become incompliant with the regulations. Even if vaccines are approved, the need for antiviral agents against SARS-CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 39 publications
4
40
0
Order By: Relevance
“…In line with our findings, a recent report demonstrated the activity of amantadine against SARS-CoV-2 in VeroE6 cells with EC50 of 83–119 µM [ 32 ]. Our study adds novel knowledge to the field by also investigating rimantadine and memantine, both showing potency superior to amantadine.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our findings, a recent report demonstrated the activity of amantadine against SARS-CoV-2 in VeroE6 cells with EC50 of 83–119 µM [ 32 ]. Our study adds novel knowledge to the field by also investigating rimantadine and memantine, both showing potency superior to amantadine.…”
Section: Discussionsupporting
confidence: 92%
“…The activities of the compounds showing the highest affinity for the RBD were investigated using an ELISA-based test involving immobilized ACE2-His-tag protein on nickel-coated microplates [51][52][53]. This experiment enables the study of the effect of a ligand on the assembly generated by the interaction of RBD with ACE2.…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…While all studies agree on an overall cation selectivity of the channel, there is no consensus on its preference for K + over Na + [21] and whether it is at all permeable to Ca 2+ [17, 21]. In some of these studies it was reported that E-protein-mediated channel fluctuations were inhibited by the antiviral channel blocker amantadine or hexamethylene-amiloride (HMA), and the presence of these compounds also resulted in an attenuation of virus replication in vivo [11,19, 22, 23]. Because of the heterogeneity in the functional data, it is currently difficult to interpret these pharmacological results in the context of a defined channel activity of the E-protein.…”
Section: Introductionmentioning
confidence: 99%